Governance for disaster risk reduction: development of standard operating procedure during flood disaster in hemodialysis patients - Adnan, Azreen Syazril (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
The recent flood had affected many healthcare facilities, including the hemodialysis centers. End Stage Renal Failure (ESRF) patients are hemodialysis dependent depriving them from treatment may lead to increased morbidity and mortality. A specific Standard Operating Procedure (SOP) is required during disaster for hemodialysis services to ensure treatments are not disrupted. During our recent flood in Kelantan. we have identified several issues on human resources poor coordination, missing patients' clinical records, logistic issues for patient and medical supply transfer and unsupervised dialysis quality control as the major problems. This research is meant to develop a SOP for the hemodialysis staffs and patients during disaster. to ensure mitigation, preparedness, response and recovery process successful. The SOP will be developed in 4 phases. namely: Phase 1: identification of stakeholders and the experts and establishing working groups for specific areas (i.e.: human resources management development of web based medical data records. logistics coordination and dialysis quality control). Phase 2: Workshops and Guideline Reviews by the assigned working groups and development of web based medical record system for hemodialysis patients. Phase 3 SOP development and consensus by the stakeholders. Phase 4: SOP Review and Approval (application of the SOP in a drill) The SOP developed from this study will be applied during flood disaster and the web based medical records will be referred in the clinical management of the patients. The outputs of this study will reduce mortality and prevent morbidities in patients on regular hemodialysis and will ensure the continuity of care with acceptable quality of service during disaster. Complications related to dialysis treatments can also be prevented and reduced with effective coordination of human resources and logistics A specific Standard Operating Procedure (SOP) is required during disaster for hemodialysis services to ensure treatments are not disrupted.